Crosland and New Labour
XII, 207 p.
Keywords: How much does Tony Blair owe to Anthony Crosland? The author of The Future of Socialism , who died suddenly as Foreign Secretary in 1977, remains the major philosophical inspiration and reference point for the left. To what extent is New Labour fashioned in Crosland's image? What can the Blair government learn from his writings and ministerial achievements? An all-star cast of sixteen authors examine Crosland's legacy in political theory and political practice and point to numerous ways in which his message remains relevant to policy-makers today. The contributors include Gordon Brown, Roy Hattersley, Michael Young, Raymond Plant, David Lipsey, Brian Brivati and Tony Wright. Susan Crosland contributes a moving postscript.